The Importance of Dhiker in the Book Tanweer Al- Salkeen wa Targheeb al-Talbeen by Abd-alkareem Wali al-Din: Verification and study - Fateh, Kaylan Muhammed; Hamada Saleh al-Jubouri, AUday Jassim (Journal of Tikrit University for Humanities, 2023)
After this trip in deep science among its masters in which I spent the quite a long time investigating for being blessed by the grace and facilitate the completion of this thesis, I summarize the most important results of the study as follows: God's mercy was born in the first quarter of the fifth century AH and lived until the end of the third quarter of the fifth century AH. The birth year was 705 AH. . The historical books did not mention anything about his family, whether a spouse or children. Perhaps mostly because he was not married for preoccupation with science and travel.. family's that has a share of science and religion, his father was memorizer of the Holy Qur'an. like other predecessors journeyed to the places and the country's searching for information. After studying models of narrators through tracking, his approach was characterized by equity, accuracy after the investigation and the search then judged including deserves respect the right to speak and the weak . Finally, we ask God to have mercy on us His mercy and Eskinna Pfchrist in peace and thank God .